Structural Integrity Assessment of Weld for Joining Waveguide to Annular Linear Induction Pump Subjected to Vibration - Ashish Kumar; Y.V.Nagaraja Bhat; B.K. Sreedhar; S.I. Sundar Raj; V. Prakash; P. Selvaraj (Fracture and Structural Integrity)
Annular Linear Induction Pump (ALIP) is employed for low flow rate pumping of liquid metals because of its maintenance free operation. In order to monitor pump vibration during operation, a waveguide with accelerometer combination is employed. The waveguide is a Stainless Steel (SS) rod of 300 mm length and 20 mm diameter which is provided with a threaded provision at one end for mounting the accelerometer. The other end of the waveguide is welded to the shell of the ALIP of 3 mm thickness. These waveguides are to be attached to the ALIP in different orientations. The weld connecting the waveguide to the shell of ALIP is subjected to fatigue loading caused due to pump vibration. This paper discusses the analysis carried out to determine the fatigue life of the weld using ASME SECTION VIII DIVISION 2.